2020
DOI: 10.3389/fncel.2020.00126
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Modulates Excitatory Synaptic Transmission by Activating Presynaptic D1-like Dopamine Receptors in the RA Projection Neurons of Zebra Finches

Abstract: Songbirds are useful vertebrate study models for vocal learning and memory. The robust nucleus of the arcopallium (RA) receives synaptic inputs from both the posterior and anterior pathways of the song control system in songbirds. Hence, RA plays an important role in the control of singing. RA receives dopaminergic (DArgic) inputs that increase the excitability of RA projection neurons (PNs). However, the effects of DA on excitatory synaptic transmission are yet to be deciphered. In this study, the effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Excitatory cells predominantly expressed various GABAergic and serotonergic receptor classes and primarily expressed some dopaminergic (DRD3) and cholinergic (CHRM5) receptors, with RA-specific Excit_1 primarily expressing GABRE, whereas inhibitory cells primarily expressed other GABAergic subunits, with Inhib_2 primarily expressing GABRG1, CHRM2, and DRD2 ( Figure S7A ). These findings indicate different synaptic specializations of various cell types and provide a cellular basis for the differential expression of various neuromodulatory receptors in RA, 20 , 77 80 insights into likely cellular target of action of related drugs known to affect RA physiology, 48 , 78 , 81 84 and predictions for cell type-specific effects for future pharmacological studies. As for axonal guidance and connectivity, several genes were differential in excitatory (e.g., ADCYAP1, SEMA3F, CDH17, DCN) vs. inhibitory (e.g., SLIT2, RELN, SEMA3A/C/E, UNC5C) cells ( Figure S7B ).…”
Section: Resultsmentioning
confidence: 72%
“…Excitatory cells predominantly expressed various GABAergic and serotonergic receptor classes and primarily expressed some dopaminergic (DRD3) and cholinergic (CHRM5) receptors, with RA-specific Excit_1 primarily expressing GABRE, whereas inhibitory cells primarily expressed other GABAergic subunits, with Inhib_2 primarily expressing GABRG1, CHRM2, and DRD2 ( Figure S7A ). These findings indicate different synaptic specializations of various cell types and provide a cellular basis for the differential expression of various neuromodulatory receptors in RA, 20 , 77 80 insights into likely cellular target of action of related drugs known to affect RA physiology, 48 , 78 , 81 84 and predictions for cell type-specific effects for future pharmacological studies. As for axonal guidance and connectivity, several genes were differential in excitatory (e.g., ADCYAP1, SEMA3F, CDH17, DCN) vs. inhibitory (e.g., SLIT2, RELN, SEMA3A/C/E, UNC5C) cells ( Figure S7B ).…”
Section: Resultsmentioning
confidence: 72%
“…The methods of using zebra finches were authorized by the Institutional Animal Care and Use Committee of Jiangxi Science and Technology Normal University (3601020137931). Then, 300-μm-thick coronal brain slices were obtained from adult male zebra finches (Wang et al, 2020 ). The bird was anesthetized with isoflurane and decapitated.…”
Section: Methodsmentioning
confidence: 99%
“…The pipette capacitance and series resistance were quickly compensated using MultiClamp 700B (Molecular Devices, CA, USA), which was monitored at 2-min intervals. The signals were amplified, filtered (2 kHz), and digitized (10 kHz) using a MultiClamp 700B amplifier attached to a Digidata 1550 system and a computer using the pCLAMP version 10.7 software (Wang et al, 2020 ). The membrane potentials were corrected for a liquid junction potential of +5 mV.…”
Section: Methodsmentioning
confidence: 99%
“…This event is critical to triggering the synthesis of PRPs (Moncada et al, 2011). Although dopamine acts on D1Rs (D1/D5) or D2‐family receptors (D2Rs) (D2/D3/D4), behavioural studies have confirmed that activation of hippocampal D1Rs is essential for memory encoding (Hagena & Manahan‐Vaughan, 2016; Pezze et al, 2015) and LTM formation (Moncada & Viola, 2007; O'Carroll et al, 2006; Rossato et al, 2009), whereas D2Rs do not seem critical in these memory processes (Feyissa et al, 2019; Hagena & Manahan‐Vaughan, 2016; Wang et al, 2020).…”
Section: Introductionmentioning
confidence: 94%